2005
DOI: 10.1371/journal.pmed.0020322
|View full text |Cite
|
Sign up to set email alerts
|

Why Medical Students Are Crucial to the Future of Research in South Asia

Abstract: One long-term strategy for promoting health research in developing countries is to target medical students early in their careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
131
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 10 publications
4
131
0
11
Order By: Relevance
“…Training in health research forms an important part of medical education [1], while students' research can contribute to the published output of an institution. It is essential to inculcate critical thinking and reasoning skills and to develop a positive attitude among resident physicians towards their scientific research during their medical career [2].…”
Section: Introductionmentioning
confidence: 99%
“…Training in health research forms an important part of medical education [1], while students' research can contribute to the published output of an institution. It is essential to inculcate critical thinking and reasoning skills and to develop a positive attitude among resident physicians towards their scientific research during their medical career [2].…”
Section: Introductionmentioning
confidence: 99%
“…In many South Asian countries, research component has not been made mandatory in the medical curriculum. [15] Studies reported that some of the medical schools in India, Pakistan and Nepal also conducted research projects and community based epidemiological studies during their studentship and internship though it has not become an integral part of the medical curriculum. [16] The lack of research methodology and the absence of qualified researchers hinder many developing countries to conduct health research by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, this may reflect insufficient time dedicated to research activities, as the medical curricula are very demanding of time, or this partial scientific achievement may reflect inadequate mentoring. Additionally, expectations of low salary compensation in research could deter medical students from pursuing scientific careers; thus, by graduation they are not dedicating much time to research and might tend to shift their focus to clinical interests (2) . All these aspects combined may limit the recruitment of potential scientists who, otherwise, could be identified in their positive scientific experiences during their graduate studies (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Research experience may develop students' skills in independent learning, critical assessment of medical literature, and writing scientific papers (2) . If such experience is not provided, the result may be a lack of basic research capabilities, thus hampering these abilities and leading to the production of professionals who are less inclined to think as they practice (3) -a factor that, among other social and economic conditions, could be associated with low quality in medical care.…”
Section: Introductionmentioning
confidence: 99%